2013
DOI: 10.1242/dev.090589
|View full text |Cite
|
Sign up to set email alerts
|

Molecular causes of aneuploidy in mammalian eggs

Abstract: SummaryMammalian oocytes are particularly error prone in segregating their chromosomes during their two meiotic divisions. This results in the creation of an embryo that has inherited the wrong number of chromosomes: it is aneuploid. The incidence of aneuploidy rises significantly with maternal age and so there is much interest in understanding this association and the underlying causes of aneuploidy. The spindle assembly checkpoint, a surveillance mechanism that operates in all cells to prevent chromosome mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
162
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 94 publications
7
162
0
Order By: Relevance
“…41 In principle, a reduction in either Mad2 or pAurora C, could influence the fidelity of bivalent segregation at the end of MI. This is supported by the observations that when individual SAC proteins are reduced or knocked-out in oocytes, rates of aneuploidy in the resulting eggs are raised, 1,15,17,42 and when young oocytes are cultured with the Aurora kinase inhibitor ZM447439, a significant reduction in kinetochore pAurora C (Fig. S2A) and a rise in aneuploidy at MI completion are both measured (Fig.…”
Section: Aged Oocytes Have a Reduced Ability To Arrest With Low-dose supporting
confidence: 58%
See 3 more Smart Citations
“…41 In principle, a reduction in either Mad2 or pAurora C, could influence the fidelity of bivalent segregation at the end of MI. This is supported by the observations that when individual SAC proteins are reduced or knocked-out in oocytes, rates of aneuploidy in the resulting eggs are raised, 1,15,17,42 and when young oocytes are cultured with the Aurora kinase inhibitor ZM447439, a significant reduction in kinetochore pAurora C (Fig. S2A) and a rise in aneuploidy at MI completion are both measured (Fig.…”
Section: Aged Oocytes Have a Reduced Ability To Arrest With Low-dose supporting
confidence: 58%
“…Reduced SAC with maternal age A functional SAC is essential for faithful chromosome segregation in both mitosis and meiosis, 12,13 and interruption of SAC components in mouse oocytes, such as Mad2 or Aurora C, accelerates meiotic progression and increases aneuploidy rates. 1,15 In fact we have recently observed that SAC proteins have functions that last the entire period of MI, not just the canonical period of prometaphase, and are essential in slowing down the time taken to complete MI-a phenomenon that promotes bivalent biorientation and reduces mis-segregation. 66 However, whether a defective SAC is involved in aged mouse oocytes remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During embryonic development, primordial germ cells migrate from the primitive streak through the endoderm to the genital ridge where they differentiate into oogonia while the foetal ovary forms (Richardson & Lehmann 2010). After the initial burst of oogonial proliferation, the cells begin meiosis, but the process is arrested in prophase-I (Jones & Lane 2013). The arrested oocytes initially form clusters and then become encapsulated in pre-granulosa cells, forming a structure known as the primordial follicle, which represents a dormant, non-growing state (Kerr et al 2013).…”
Section: Introductionmentioning
confidence: 99%